Finance for development : Latin America in comparative perspective - Stallings, Barbara; Studart, Rogério, 1961-; United Nations. Economic Commission for Latin America and the Caribbean (Washington, D.C. : Brookings Institution Press, 2006)
"Access to finance is a critical element in any effort to promote development in emerging market economies. In this analysis of the Latin American financial sector, Barbara Stallings and Rogerio Studart examine recent transformations in the region, compare them to related developments elsewhere, and consider where they might lead. They challenge the new literature on finance and development, which argues for the elimination of public-sector banks, substitution of private monitoring for government regulation and supervision, and more complete integration with international capital markets. Rather, the authors advocate a more balanced approach that emphasizes individual country situation and strengthens the institutional context in which financial systems operate." "Case studies illustrate changes occurring in Chile, Mexico, and Brazil - the most sophisticated financial systems in Latin America. The authors place particular emphasis on the need to overcome two types of market failure: the lack of long-term finance for investment and access to credit for small firms. They conclude with policy recommendations for strengthening Latin American banks and capital markets so that they can play a greater role in supporting economic development."--Jacket
Finance for development: issues and trends -- Finance within a new development model in Latin America -- Latin America's financial sector today: stylized facts -- Substantive and methodological contributions -- Overview of the book --Changes in Latin America's financial system since 1990: comparisons with East Asia -- Financial liberalization, crisis, and the aftermath -- Financial liberalization: literature and hypotheses -- Financial liberalization: empirical trends -- Financial liberalization and crisis -- Rescue programs: costs and outcomes -- Conclusions -- Changes in ownership: public, private, and foreign banks -- Bank ownership and institutional environment: literature and hypotheses -- Trends in bank ownership -- Ownership and performance -- Ownership, institutions, and performance -- Conclusions -- Toward stability: regulation, supervision, and the macroeconomic context -- Regulation and supervision: literature and hypotheses -- Regulation and supervision: the state of the art -- Regulation, supervision, and financial performance -- Conclusions -- From banks to capital markets: new sources of finance -- Capital market performance: literature and hypotheses -- Comparing financial market trends across regions -- Analysis of financial market trends -- Conclusions -- The impact of the new financial system on investment and access in Latin America -- Chile: mixed ownership provides a new model -- Liberalization, crisis, and response -- Changes in structure -- Finance, investment, and growth -- Access to finance for small firms -- Conclusions -- Mexico: foreign banks assume control -- Liberalization, crises, and response -- Changes in structure -- Finance, investment, and growth -- Access to finance for small firms -- Conclusions -- Brazil: public banks continue to play a key role -- Liberalization, crises, and response -- Changes in structure -- Finance, investment, and growth -- Access to credit by small firms -- Conclusions -- Policy recommendations for a stronger financial system -- A policy agenda for the financial sector -- Banks and capital markets since 1990 -- Toward a policy agenda on finance -- Final comments.
"United Nations. Economic Commission for Latin America and the Caribbean."
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Finance -- Latin America; Finances -- Amérique latine; BUSINESS & ECONOMICS -- Finance; BUSINESS & ECONOMICS -- Economics -- Comparative; Finance; Latin America